Kontinuitas Gambar Adegan Dalam Penyutradaraan Drama Televisi â€œKuwi Nggonkuâ€ - Hasanuddin, Alfin Nur; Murbaningsih, Ari Mintarti (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
The television drama â€œKuwi Nggonkuâ€ is an interesting drama show. This drama applies image continuity in several scenes. There are four types of continuity, namely Content Continuity, Movement Continuity, Position Continuity, and Dialogue Continuity. The television drama â€œKuwi Nggonkuâ€ tells the story of social conflicts that exist in society, specifically regarding the orderliness in the cleanliness of public toilets. In creating this production work, the method used is 3 stages of production, namely pre-production, production, and post-production (including evaluation). The implementation of image continuity in the television drama Kuwi Nggonku aims to maintain image balance so that it does not jump and convey the character's mood well, supported by cut in and cut away editing techniques. The implementation of image continuity in this production results ; Continuity in the production of â€œKuwi Nggonkuâ€ makes it easier for the audience to understand the story line, Continuity of the images also supports strengthening the conflict of the story being created, the more the continuity of the images is maintained, the more it will support the audience to be able to focus on the conflict.